A Work study on MEQ Industries - Canusa, Riezel (College of Engineering, 1996)
MEQ Industries is a small, family-owned enterprise that specializes in exporting rattan baskets to Japan. They ship year round but their peak months are from January to March, in time to coincide with spring and the Japanese Cherry Bloom Festival. The team, through interviews and immersion visits, discovered that the main problem MEQ Industries, aside from material shortage, is the in-process delays of the company. The group further determined that isolating spoking and framing processes will illustrate that delays as a whole and that recommendations can be derived from the analysis of these two processes. Upon completion of their investigation, the team set forth the following immediate recommendations : a) the elimination or merging of several steps in the two processes; b) the reduction of batch size for framing and the elimination of batches in spoking; c) the redesigning of work areas and workstations; and d) the use of a variable jig table for the drilling operations. The following long term recommendations were also made : a) a new plant layout and b) the increase in the number of fire extinguishers.